Augmented intelligence for open education: bridging the digital gap with inclusive design methods - Alvarez-Icaza, Inés; Huerta, Omar (Frontiers in Education, 2024)
Augmented Intelligence development with an inclusive vision will not happen without the design theory and committed practice, but neither can it be carried out from a biased in-a-silo design vision.The application of DM4O design methodology, allows envisioning diverse scenarios to conceptualise inclusive digital educational platforms as key resources to bridge learners digital gap in a global context. Aligned with SDG 4, the objective of this study is to identify potential higher education (Hi-Ed) students' limitations when interacting with an open education digital platform (OE-DP), to propose a set of inclusive design guidelines. Following a mixed methods approach, this chapter sets the state of the art across a systematic literature review; then presents the DM4O design method as the collecting data tool; and finally, reports the results of a survey application, to record the perceived limitations experienced by Hi-Ed students as users of an OE-DP. This study marks valuable insights for designers, educators, and institutions administrators, towards a digital transformation encouraging inclusive OE-DPs innovation in three dimensions: a) inclusive guidelines for digital platforms; b) a comprehensive list of interaction tasks suitable for digital platforms; and c) the potential limitations that these platforms must cover during the conceptualization process.